Fetal sex and maternal insulin resistance during mid-pregnancy: a retrospective cohort study - Hiroshi Yamashita; Ichiro Yasuhi; Megumi Koga; So Sugimi; Yasushi Umezaki; Misao Fukuoka; Sachie Suga; Masashi Fukuda; Nobuko Kusuda (BMC, 2020)
Abstract Background Recent studies have suggested that fetal sex influences maternal glucose and insulin metabolism during pregnancy. We examined whether fetal sex is associated with maternal insulin resistance and the β-cell function during mid-pregnancy. Methods This retrospective study included singleton pregnant women who underwent a 75-g oral glucose tolerance test (OGTT) at 24-34 weeks of gestation due to positive diabetic screening. In addition to plasma glucose (PG), we measured plasma insulin during the OGTT to obtain surrogate indices associated with insulin resistance (IR), including homeostasis assessment model (HOMA) -IR and insulin sensitivity index (IsOGTT), and β-cell function, including insulinogenic index (II), HOMA-β, and area under the curve of insulin response. We compared these indices between women carrying male fetuses to those carrying female fetuses. Results The study population included 617 women (mean age, 32.4 ± 4.9 years) with a mean pre-pregnancy body mass index (BMI) of 22.6±4.5. They underwent the 75g-OGTT at 29.0 ± 2.5 weeks. Two hundred fifty-eight (42%) women were diagnosed with gestational diabetes (GDM). There was no significant difference in maternal age, pre-pregnancy BMI, gestational age at OGTT, PG at OGTT, or the prevalence of GDM between women with a male fetus (n=338) (male group) and those with a female fetus (n=279) (female group). Regarding the indices of IR, IR was significantly higher and insulin sensitivity was lower in the female group than in the male group (HOMA-IR: 7.0 [5-9.6] vs. 6.2 [4.6-8.8], p< 0.05; IsOGTT: 5.86 [4.29-7.83] vs. 6.29 [4.59-8.84], p< 0.01) (median [quartile range]). These differences remained significant after adjustment for maternal age, pre-pregnancy BMI, gestational age and fasting PG at OGTT, and the diagnosis of GDM. In contrast, the β-cell function did not differ between the two groups. Conclusion Maternal IR during mid-pregnancy was significantly higher in women carrying a female fetus than in those with a male fetus. The sex of the fetus may affect maternal insulin sensitivity during mid-pregnancy.